The Resilience of Sufi Spiritual Behavior in Society in the 5.0 Era Increases Subjective Well-Being - saliyo sali liyo (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2023)
Abstract: From time to time, the pattern of human life continues to change. These changes started from the Stone Age until now, in the era of society 5.0. These changes have a purpose for the welfare of humanity. Changes in lifestyle from time to time cannot be separated from challenges and problems. Someone who is not able to adapt will be evicted separately. Conversely, someone who is able to survive in his life through every change will find satisfaction in his life. Sufi spiritual behavior is a safe choice of behavior to live life in the era of society 5.0 as resilience. There are several ways of building resilience in Sufi spiritual behavior to increase psychological well-being, also known as subjective well-being. The resilience of Sufi spiritual behavior includes training the ego (self-emotion) to resist the demands of the id (lust), strengthening faith, living as a blessing, and always surrendering to God. Such resilience is integrated into his personality so that his life is calm and his mind is not toying with him. Someone who chooses the resilience of Sufi spiritual behavior has a strong power to live life. The person is happy despite all difficulties and grateful for the abundance of God's grace. In the end, the person's subjective well-being increases